2012
DOI: 10.1016/j.topol.2011.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Lindelöf spaces which are indestructible, productive, or D

Abstract: We discuss relationships in Lindelöf spaces among the properties "indestructible", "productive", "D", and related properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 32 publications
0
37
0
1
Order By: Relevance
“…The remainder of this paragraph assumes that d = ℵ 1 . Aurichi and Tall [3] improved several earlier results by proving that every productively Lindelöf space is Hurewicz. It was later shown that every productively Lindelöf space is productively Hurewicz and productively Menger [18,Theorem 8.2].…”
Section: Filter-menger Spacesmentioning
confidence: 73%
“…The remainder of this paragraph assumes that d = ℵ 1 . Aurichi and Tall [3] improved several earlier results by proving that every productively Lindelöf space is Hurewicz. It was later shown that every productively Lindelöf space is productively Hurewicz and productively Menger [18,Theorem 8.2].…”
Section: Filter-menger Spacesmentioning
confidence: 73%
“…By [3,Theorem 23] and [20,Theorem 18], every productively Lindelöf space has the Hurewicz property if d = ω 1 or add(M) = c. The following theorem implies both of these results. The Filter Dichotomy is the statement that for any non-meager filters F , G on ω there exists a monotone surjection φ : ω → ω such that φ(F ) = φ(G).…”
Section: Introductionmentioning
confidence: 79%
“…(2) ⇒ (1). By Theorem 7 in [7], a metrizable space is indestructibly productively Lindelöf if and only if it is σ-compact.…”
Section: The Tall's Diagram Inmentioning
confidence: 99%